Molecular Deregulation of EPAS1 in the Pathogenesis of Esophageal Squamous Cell Carcinoma - Islam, Farhadul; Gopalan, Vinod; Law, Simon; Lam, Alfred K.; Pillai, Suja (Frontiers in Oncology, 2020)
Endothelial PAS domain-containing protein 1 (EPAS1) is an angiogenic factor and its implications have been reported in many cancers but not in oesophageal squamous cell carcinoma (ESCC). Herein, we aim to examine the genetic and molecular alterations, clinical implications and functional roles of EPAS1 in ESCC. High resolution melt-curve analysis and Sanger sequencing were used to detect mutations in EPAS1 sequence. EPAS1 DNA number changes, mRNA expressions were analysed by a polymerase chain reaction. In-vitro functional assays were used to study the impact of EPAS1 on cellular behaviours. Overall, 7.5% (n=6/80) of patients with ESCC had mutations in EPAS1 and eight novel variants (c.1084C>T, c.1099C>A, c.1145_1145delT, c.1093C>G, c.1121T>G, c.1137_1137delG, c.1135_1136insT and c.1091_1092insT) were detected. Among these mutations, four were frameshift (V382Gfs*12, A381Lfs*13, K379Ifs*6 and K364Nfs*12) mutations and showed the potential of nonsense-mediated mRNA decay in computational analysis. Majority of patients had shown molecular deregulation of EPAS1 (45% [n=36/80] DNA amplification, 42.5% [n=34/80] DNA deletion as well as 53.7% [n=43/80] high mRNA expression, 20% [n=16/80] low mRNA expression). These alterations of EPAS1 were associated with tumour location and T-stages. Patients with stage III ESCC having EPAS1 DNA amplification had poorer survival rates in comparison to EPAS1 DNA deletion (p=0.04). In addition, suppression of EPAS1 in ESCC cells showed reduced proliferation, wound healing, migration and invasion in comparison to that of control cells. Thus, the molecular and functional studies implied that EPAS1 plays crucial roles in the pathogenesis of ESCC and has the potential to be used as a prognostic marker and as a therapeutic target.